Supporting University Ventures in Nanotechnology, Biomaterials and Magnetic Sensing Applications Policies, Practices, and Future (Springer International Publishing, 2018)
This book investigates the transfer of technology from basic research to society. When transferring technology, two main ways may arise: licensing out the further exploitation rights straight from the University departments to the industry or joining the technology a step beyond into market applications for products and services development, through spin-off and startup companies. This book focuses on the second process and the stakeholders involved, with several study cases from real life. Profiles of research entrepreneurs are described, along with categories and general characteristics of entrepreneurial infrastructure. Different phases of launching university ventures are presented, as well as currently perceived technology transfer systems. Important practical considerations for IP protection are included. Case studies of research transfer are shortly given, related to nanotechnology, biomaterials and magnetic sensing applications. The book was written by experts in the field with extensive practical experience in both academic and entrepreneurship real life cases, thus being able to uniquely integrate both approaches to spin-offs and startups.